The pathogenesis of burn wound conversion - Singh, Vijay; Devgan, Lara; Bhat, Satyanarayan; Milner, Stephen M (Annals of plastic surgery, 2007)
Burn wound progression is a poorly understood process by which certain superficial partial-thickness burns spontaneously advance into deep partial-thickness or full-thickness wounds. Progression of an injury into deeper tissue is an important phenomenon in the treatment of thermal injury due to the fact that burn wound depth may be a significant determinant of morbidity and treatment. This article reviews current knowledge of the pathogenesis, molecular and cellular mechanisms, local and systemic factors, and treatment modalities related to wound conversion. All peer-reviewed, original, and review articles published in English-language literature relevant to the topic of burn wound conversion on animals and human subjects were selected for this review. After assessing data relevance, independent extraction by a sole reviewer was performed. Data were tabulated according to the following categories: pathogenesis, mechanisms, local and systemic factors, and treatment. Burn wound progression is complex and caused by additive effects of inadequate tissue perfusion, free radical damage, and systemic alterations in the cytokine milieu of burn patients, leading to protein denaturation and necrosis. Even though insufficient evidence exists for causal inferences, infection, tissue desiccation, edema, circumferential eschar, impaired wound perfusion, metabolic derangements, advanced age, and poor general health play important roles. Although consensus-building research is ongoing, current mainstays of treatment include adequate fluid resuscitation, nutritional support, and local wound care, with an emphasis on topical antimicrobial agents and biosynthetic dressings. Identifying early indicators by elucidating possible interacting or synergistic mechanisms and by developing preventative strategies will enhance prevention and treatment.